The Interplay Between ESG Disclosure And Financial Profitability - Rizqo, Muhammad; Qadri, Resi Ariyasa (Pusat P2M Politeknik Negeri Batam, 2024)
This study seeks to elucidate the correlation between the enactment of environmental, social, and governance (ESG) pillars and financial profitability. A total of 275 samples were amassed from 55 corporations listed on the Indonesia Stock Exchange, chosen via the purposive sampling technique. The ESG scoring data employed in this investigation was evaluated following the criteria set forth by Thomson Reuters Eikon. To examine the nexus between profitability and the ESG pillars, this research utilized the panel data regression methodology. The theoretical framework guiding hypothesis formulation was the resource-based view theory. The findings of this inquiry reveal that the environment, social, and governance variables exert a significant positive impact on corporate profitability. The implications of these findings suggest that this research could act as a pivotal consideration for corporations to integrate non-financial performance indicators within their operational strategies. Furthermore, the outcomes of this study provide investors with a metric to gauge the potential and efficiency of companies in achieving optimal profitability.